Dampak Ekologis Implementasi Blockchain Dan Cryptocurrency Di Era Digital - Rico Cito Purba; Marince Lumbanraja; Agnes Ulina Raelsi Raja Gukguk; Wesly Varrey; Tevia Oktavia Manalu; Joosten (JURNAL ILMIAH SAINS TEKNOLOGI DAN INFORMASI, 2024)
Blockchain and cryptocurrencies have changed the way we transact and interact in the digital age. However, the rapid advancement of these technologies has resulted in major environmental impacts. Efficient implementation of blockchain requires the use of large amounts of energy and computing power, with consensus algorithms as the foundation. The purpose of this study is to investigate the environmental implications of blockchain and cryptocurrency implementation, as well as initiatives to mitigate these issues. The type of research is a library study (library research) using a qualitative method, namely by combining, collecting information or previous scientific papers on relevant topics. Along with the growing popularity of cryptocurrencies, the continuous mining process often results in large energy consumption and carbon emissions, sparking concerns about their long-term viability and environmental impact. Based on the results of previous research and research sources, the author found a solution to the problem of high energy consumption from the use of blockchain, namely: Proof of Stake (PoS), Proof of Authority (PoA), Sidechains and Layer-2 Solutions, Hardware Optimization, Implementation of Consensus Algorithms Based on RUST.